The Preparedness Of Kph Dolago Tanggunung In Implementation Of Social Forestry Policy In Bakubakulu Village, Sigi Regency - Inggrid Inggrid; Adam Malik; Golar Golar (Universitas Tadulako, 2019)
This study aims to determine the preparedness of KPH Dolago Tanggunung in the implementation of social forestry policy, and to know the preparedness of the community toward forest management through social forestry scheme. This research was conducted at Kilo Village, Sigi District, Central Sulawesi Province from September up to November 2016. Data were analyzed using qualitative approach, through scaling 1-3-5 (Modified Likert Scale). The parameters which were measured were the FMU's readiness in the implementation of the boundary structure, forest inventory covering: status, use and land cover, climate, human resources and demography, species of flora distribution, population type and fauna habitat, socioeconomic conditions, block division (biophysical characteristics field, potential of natural resources, the existence of rights or business permits and utilization), the division of the block includes:productivity and potential of the area, the design of the area for utilization while from the preparedness of the community was assessed based on understanding and community involvement itself. The result of the research showed that KPH Dolago Tanggunung was ver ready toward the implementation of Social Forestry policy that can be proved by the fulfillment of several criteria and indicators of KPH readiness. Meanwhile, the community was also well-prepared in the management of Community Forest based on the level of understanding and response to their involvement in the implementation of the program.